Land Suitability Evaluation for New Paddy Rice Field in Mukomuko District - Albert Carles; Kanang Setyo Hindarto; Heru Widiyono; Mukhtasar Mukhtasar; Hermansyah Hermansyah (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2021)
This study aims to identify the physical, chemical characteristics of the soil and determine the suitability of rice fields for new openings in Mukomuko. This research was conducted from September to October 2019, which consisted of fieldwork and laboratory analysis. This research uses a survey method, soil sampling is carried out by a composite method consisting of 5 soil samples. Composite soil sampling technique based on land unit work maps produced from the map of soil types Mukomuko district scale of 1: 100.000. The results showed that all samples had the same dominant limiting factors namely P2O5, K2O, and Base Saturation. Land suitability for lowland rice plants in Mukomuko District Af.1.2.1 (S3nr) land area with an area of 42.68 ha, Af.1.2.2 (S3nr) land area with an area of 56.65 ha, land unit Tf.2.1 (S3nr) with an area of 60.15 ha, and land unit Tf.3.1 (S3nr) with an area of 89.30 ha.